Ivabradine: A Potential Therapeutic for Children With Refractory SVT - Younis, Nour K.; Abi-Saleh, Bernard; Al Amin, Farah; El Sedawi, Omar; Tayeh, Christelle; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2021)
Background: In April 2015, ivabradine was approved by the Food and Drug Administration for the treatment of patients with coronary artery disease and heart failure (HF). The use of this medication has been linked with improved clinical outcomes and reduced rates of hospitalization in patients with symptomatic HF and a baseline heart rate of 70 bpm and above. Nonetheless, little is known about the use of ivabradine in pediatric patients with supraventricular tachycardia (SVT). This use is not well-studied and is only endorsed by a few case reports and case series. Aim: This study discusses the off-label utilization of ivabradine in pediatric patients with SVT, and highlights its efficacy in treating treatment-resistant (refractory) SVT. Methods: We conducted a retrospective single-center observational study involving pediatric patients with SVT treated at our center between January 2016 and October 2020. We identified the total number of patients with SVT, and the number of patients with refractory SVT treated with Ivabradine. Similarly, we performed a thorough review of the databases of PubMed, Medline and Google Scholar to compare the clinical course of our patients to those described in the literature. Results: Between January 2016 and October 2020, 79 pediatric patients with SVT were seen and treated at our center. A treatment-resistant SVT was noted only in three patients (4%). Ivabradine was used in these patients as a single or combined therapy. The rest (96%) were successfully treated with conventional anti-arrhythmics such as β-blockers, flecainide, and other approved medications. In the ivabradine group, successful reversal to sinus rhythm was achieved in two of the three patients (66%); one patient was treated with a combination therapy of amiodarone and ivabradine, and the other patient was treated only with ivabradine. Conclusion: Overall, promissory results are associated with the use of ivabradine in pediatric patients with refractory SVT. Ivabradine appears to be a safe and well-tolerated medication that can induce adequate suppression of SVT, complete reversal to sinus rhythm, and effective enhancement of left ventricular function.